The Impact of ESG Practices on Firm Value: a Human Resource Management and Financial Decision Perspective - Sentot E Baskoro; Dessy Evianti; Suharti; Wiwit Agustina; Dany Luqyana Idris (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of the business world that increasingly emphasizes sustainability aspects encourages companies to implement Environmental, Social, and Governance (ESG) principles as a strategy in creating long-term corporate value. This study aims to analyze the impact of ESG practices on corporate value from the perspective of human resource management and financial decision-making. This study uses a qualitative approach with descriptive methods through literature studies and analysis of company documents, such as annual reports, sustainability reports, and various relevant scientific references. Data analysis techniques are carried out through content analysis with the stages of data collection, data reduction, data presentation, and drawing conclusions. The results show that the implementation of ESG practices has a positive impact on increasing corporate value by strengthening reputation, increasing investor confidence, reducing business risks, and creating competitive advantages. From a human resource management perspective, ESG plays a role in improving employee welfare, competency development, workforce engagement, and establishing a sustainable organizational culture. Meanwhile, from a financial decision-making perspective, ESG helps companies in determining more effective investment, funding, and risk management strategies. This study concludes that the integration of ESG into corporate strategy is a crucial factor in building business sustainability and increasing corporate value in the long term.